A Method to Monitor Patients Health Status Using Web Server - Rajeshwar Rao Arabelli, P.Anuradha, Alekhya Kamarapu (International Journal of Advanced Science and Technology, 2020)
The relentless development of information and communication Technologies (ICTs) has contributed to the introduction of the Internet of Things (IoT). IoT systems make doctors and patients confident in modern healthcare as they are used in a number of medical fields (such as real time surveillance, patient information management system and health care management system). Body Sensor Network (BSN) technology is a key technology in IoT healthcare system growth, where you can monitor your patient with small, light weight wireless nodes. However, the implementation of any new technology in health application leaves the patient vulnerable, without taking into account protection. In this projrct, we highlight the main security requirements for the BSN-based healthcare system. Next, we proposed a secure health system based on IoT that uses BSN, called BSN support, which can effectively meet these requirements. Here at BSN we use different types of sensors, i.e. the temperature sensor, the heart rate sensor. The main purpose of this automatic health system and e-monitoring of ECG using webserver is to monitor the body temperature, heartbeat rate and pulse rate of a patient and display the same to the doctor by using webserver and also send sms to the care taker of the patient.